LINGUOCULTURAL ORIGINS OF OCCASIONAL UNITS - TSONYNETS, Maria (Науковий вісник Ужгородського університету. Серія Філологія, 2020)
In this article the influence of linguistic culturology on the formation of occasional newly-coined words has been analyzed. The topicality of the research lies in the linguistic and cultural peculiarities of the appearance of individual author᾽s neologisms which help to outline the features of these innovations in the consciousness of the native English speak- ers. The purpose of the article is to determine the role of the linguocultural influence on the emergence of nonce-words. The objectives of the research are: the definition of the occasional unit and linguistic culturology, the analysis of occasionalisms as the author᾽s creations and the influence of the national language model of the world. The author has tried to prove that the relationship between language and culture is presented as a key one in Modern Linguistics. Linguistic culturology investigates correlation and interference of culture and language. Language is a means of penetrating in a person᾽s mentality and culture. Culture and nation are reflected in the national language model of the world that helps to study the interaction processes of lan- guage, thinking and reality in order to understand the leading role of language in the creation and reflection of the inner world of a human being. The main attention of the research is focused on occasional unit as a formation of a particular author who is a language personality and a constituent of a particular nation. The linguistic culturology is treated as a field of knowledge, which is directly related to the study of occasionalisms. The author of such newly-coined words is a social phenomenon filled with an individual aspect, that is formed through the internal attitude towards the language and the establishment of personal linguistic meanings. It was substantiated that each occasional unit contains definite information indicating the author of the formed innovation that reflects the cultural and historical features of a particular nation. Therefore, the study of the occasional units in terms of national and cultural specificity in our time is relevant and important. It contributes to a better understanding of the culture and thinking of the nation. It should be noted that the influence of the national language image of the world on the formation of occasional vocabulary is significant.